Narratives of Pain and Power : Chimamanda Ngozi Adichie’s Feminist Reckoning with Gender-Based Violence and Patriarchal Oppression - Ms. Ishita Bhatt (South Eastern European Journal of Public Health, 2025)
This study undertakes a critical examination of gender-based violence and patriarchal hegemony as incisively depicted in the literary corpus of Chimamanda Ngozi Adichie. Through a feminist epistemological framework, it interrogates the thematic undercurrents of Purple Hibiscus, Half of a Yellow Sun, and We Should All Be Feminists, elucidating their profound engagement with the systemic subjugation of women. Adichie’s oeuvre unflinchingly exposes the manifold manifestations of gendered violence—ranging from domestic brutality and psychological subordination to sexual predation and the harrowing practice of female genital mutilation—while simultaneously dismantling the sociocultural paradigms that engender female erasure. This discourse aligns with postcolonial feminist critiques, particularly those of Gayatri Spivak and Nawal El Saadawi, situating Adichie’s narratives within a broader dialectic of intersectional oppression, wherein colonial legacies, patriarchal dominance, and entrenched socio-political inequities coalesce. By reclaiming silenced narratives and transmuting them into potent articulations of resistance, Adichie not only amplifies the lived experiences of women relegated to the periphery but also catalyzes a radical reimagining of gender paradigms. This paper posits that her literary interventions transcend mere fictional representation, constituting an urgent imperative for deconstructing androcentric structures and fostering an emancipatory discourse on female agency. Ultimately, Adichie’s work emerges as an indispensable testament to feminist thought, compelling a global reckoning with the exigencies of gender justice and equitable representation.